Capstones as Transitional Experiences - Judith McNamara; Rachael Field; Sandra Coe; Des Butler (Legal Education Review)
Indigenous peoples in Australia are notably disadvantaged in the higher education context. The tertiary education sector must act constructively to increase participation rates and promote successful outcomes for Indigenous students. The Indigenisation of curriculum is a key means by which culturally competent and socially just education programs may be developed. In the legal education context, the incorporation of Indigenous-related content opens an avenue of critique of the Australian legal system and its differential impacts on Australia’s First Peoples. In this article, we review literature relating to the Indigenisation of curricula in four areas; Indigenous issues, Indigenous perspectives, Indigenous law and Indigenous law students. Following this review, we present the findings of our exploratory study, which investigated the extent to which Indigenous-related content and perspectives are incorporated into the XXXX curriculum. We represent the Indigenisation of the curriculum as a key means of broadening the scope of student enquiry, and reinforcing the centrality of justice in teaching and learning about the law.